2014
DOI: 10.1093/humrep/deu307
|View full text |Cite
|
Sign up to set email alerts
|

Patient preference for a long-acting recombinant FSH product in ovarian hyperstimulation in IVF: a discrete choice experiment

Abstract: The results of this DCE helps us to understand the trade-off women make in their preference for a long-acting rFSH product or a daily-administrated rFSH product in IVF and may support doctors when counselling patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 26 publications
2
18
0
1
Order By: Relevance
“…A number of factors such as psychological burden, physical challenge, depersonalized care, and complex injection protocol tend to impair treatment adherence 24. Efficacy (pregnancy rate), tolerability (reaction to injection pain), and convenience (dosing accuracy, ease of use, and number of injections) have been the primary points of concern for patients when choosing self-administered injection devices for IVF treatment 511…”
Section: Introductionmentioning
confidence: 99%
“…A number of factors such as psychological burden, physical challenge, depersonalized care, and complex injection protocol tend to impair treatment adherence 24. Efficacy (pregnancy rate), tolerability (reaction to injection pain), and convenience (dosing accuracy, ease of use, and number of injections) have been the primary points of concern for patients when choosing self-administered injection devices for IVF treatment 511…”
Section: Introductionmentioning
confidence: 99%
“…Features of controlled ovarian stimulation other than cost – such as effectiveness, number of injections/comfort level and convenience of administration – may have an impact on patient preference ( Palumbo et al, 2011 , van den Wijngaard et al, 2015 ). These aspects could favour the choice of corifollitropin alfa compared with rFSH.…”
Section: Discussionmentioning
confidence: 99%
“…Low-impact IVF is currently performed by administering daily FSH stimulation at dosages that are typically 25-50% reduced compared to traditional COH protocols [1,2]. However, with the advent of corifollitrophin alpha (CFA), a long acting FSH stimulant, a new alternative protocol has become possible.…”
Section: Introductionmentioning
confidence: 99%
“…Recent large randomised controlled trials have reported that corifollitrophin alpha (CFA) is an effective stimulant for controlled ovarian hyperstimulation in IVF (COH), producing pregnancy rates equivalent to traditional rFSH, but requiring significantly fewer COH stimulant injections [3,4]. While no RCT study has confirmed a patient preference for once-a-week stimulant over traditional daily rFSH approach, surveys do suggest that women prefer fewer injections provided that this approach does not compromise their IVF outcomes [2].…”
Section: Introductionmentioning
confidence: 99%